'A top secret relationship': Muslim–Christian courtships in Ceuta's convivencia. (September 2022) - Sadegh, Ibtisam
Ceuta, a Spanish enclave on the North African Mediterranean coast, is a place of quotidian coexistence between Muslims, Christians, and smaller numbers of Hindus and Jews. The Ceutan government, in response to the dense heterogeneous population, extolled discourse of convivencia, which celebrates the diverse ethno-religious groups living peacefully together. Today, convivencia permeates all aspects of Ceutan political, social, and economic life. Within this pervasive discourse, interreligious couples are regarded as the epitome of convivencia, and yet, at a familial level, they remain frowned upon for crossing socio-religious and political boundaries. This article studies how through secrecy and tactical secret-sharing, Muslim–Christian couples successfully initiate, construct, and transform their intimacy into marriage or cohabitation. Based on extensive ethnographic research and interviews with Ceutan and Ceutan-peninsular interreligious couples, this article concludes that secret courtships provide mixed couples a space and time vital for negotiating their differences, while navigating the overarching socio-religious and political structures.